New eugenol derivatives with enhanced insecticidal activity - Fernandes, Maria José Gomes (2020)
Eugenol, the generic name of 4-allyl-2-methoxyphenol, is the major component of clove essential oil, and has demonstrated relevant biological potential with well-known antimicrobial and antioxidant actions. New O-alkylated eugenol derivatives, bearing a propyl chain with terminals like hydrogen, hydroxyl, ester, chlorine, and carboxylic acid, were synthesized in the present work. These compounds were later subjected to epoxidation conditions to give the corresponding oxiranes. All derivatives were evaluated against their effect upon the viability of insect cell line Sf9 (Spodoptera frugiperda), demonstrating that structural changes elicit marked effects in terms of potency. In addition, the most promising molecules were evaluated for their impact in cell morphology, caspase-like activity, and potential toxicity towards human cells. Some molecules stood out in terms of toxicity towards insect cells, with morphological assessment of treated cells showing chromatin condensation and fragmentation, which are compatible with the occurrence of programmed cell death, later confirmed by evaluation of caspase-like activity. These findings point out the potential use of eugenol derivatives as semisynthetic insecticides from plant natural products.